Analysis of Consumer Behaviour Related to Electricity Consumption (Advances in Systems Science and Applications, 2023)
Almost three-quarters of carbon dioxide emissions originate from households' activities and among the major contributors to climate change is the energy sector. Therefore, increased attention is being paid to energy-efficient behaviour in the household segment. Over the past decades, a limited number of studies focused on the in-depth understanding of consumer behavior within energy consumption and on comparison of consumers’ own perceptions towards their effectiveness in energy consumption to the reality substantiated by the precisely measurable amounts of energy they have been consuming.  This study extends the authors' previous research on changes in consumer behavior, triggered by access to the personalized simplified and user-friendly data related to the energy consumption of a particular household. The focus is on describing the behavior patterns in electricity consumption related to consumers’ age and size of agglomeration they inhabit. The study includes data on 3 years' consumption of over 30 000 households from Slovakia. It provides conclusions relevant to the area of the Central European region at least, as among the main factors influencing the energy consumption are weather and dwelling conditions.